Agreements and accounts: On-going research on economic activities of the temple of Soknopaiou Nesos according to the Demotic texts - Lippert, S; Schentuleit, M (Harrassowitz Verlag, 2020)
At the 1st International Fayum Congress in Sommerhausen in 2003 we presented a paper on the economy of the temple of Soknopaios with results of the then still on-going five-year research project initiated by Karl-Theodor Zauzich in 2000 which aimed at the edition of the late Demotic documentary texts from Dime/Soknopaiou Nesos (30 BCE to 2nd century CE).2 At the time, our study was based mainly on ostraca and receipts pertaining to the temple’s financial administration, whereas two text types which are essential to this subject were still largely unexplored: accounts and agreements, both of which are very well represented in the Demotic material from Soknopaiou Nesos. We gave a preliminary report on the agreements at the 2nd International Fayum Congress in Lecce in 20053 , and by the end of the project, the edition volumes on ostraca and receipts were under press4 . But although Karl-Theodor Zauzich and ourselves had done preliminary work by making transliterations and translations of those accounts and agreements of which we already had photographs, the two volumes on theses texts were far from publication-ready, especially since the known source material had exponentially increased through our research in collections.